PENGARUH KOMITE AUDIT,KUALITAS AUDIT DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA DENGAN MENGGUNAKAN BENEISH M-SCORE MODEL - Fahren K, Ramdhani; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2017)
The purpose of this paper is to investigate the relationship between audit committee, audit quality, ownership structure and earnings management. In this paper, earnings management was measured by using Beneish M-Score model which consist 5 variables which are days sales in receivable index, gross margin index, asset quality index, sales growth index and total accruals to total assets to determine M-Score of each company. Research samples are Indonesian manufacturer companies listed in Indonesia Stock Exchange (IDX) by the year 2013 up to 2015 exclude companies that suffer losses, not / have not been registered in the period of observation and companies with incomplete data. The results showed that the audit committee, audit quality and ownership structure did not have a significant effect on earnings management measured using Beneish M-Score models.